Corrosion of Al2O3/Cr and Ti2O3/Cr composites in flowing air and CO2 at 750°C. (February 2021) - Nguyen, Thuan Dinh; Caccia, Mario; McCormack, Camilla K.; Itskos, Grigorios; Sandhage, Kenneth H.
Highlights: Hot-pressed Al2 O3 /Cr and Ti2 O3 /Cr composites were exposed to air and CO2 at 750 °C. Exclusive external Cr2 O3 scale growth occurred on Al2 O3 /Cr for up to 700 h at 750 °C. Finer-grained Cr2 O3 formed in CO2 on Al2 O3 /Cr, and thickened faster, than in air. Nitrides or carbides were not detected below Cr2 O3 scales formed in air or CO2 . Thick external TiO2 scales and Cr2 O3 -bearing internal oxide zones formed on Ti2 O3 /Cr. Abstract: Hot-pressed Al2 O3 /Cr and Ti2 O3 /Cr composites were exposed to synthetic air or CO2 at 750 °C. The Al2 O3 /Cr composites formed external Cr2 O3 scales, and exhibited slow parabolic oxidation kinetics, in both gases. The Cr2 O3 scales formed in CO2 possessed finer grains, and thickened at a faster rate, than Cr2 O3 scales formed in air. The Ti2 O3 /Cr composites formed thick external TiO2 scales with internal oxidation zones that also contained Cr2 O3 scales on subsurface Cr grains. After 20 h at 750 °C, the Ti2 O3 /Cr composites exhibited parabolic oxidation kinetics in both gases, although the oxidation rates were significantly higher than for the Al2 O3 /Cr composites.